Dependency of seed dormancy types on embryo traits and environmental conditions in Ribes species. (18th October 2013) - Mattana, E.; Stuppy, W. H.; Fraser, R.; Waller, J.; Pritchard, H. W.; Byers, D.
Abstract The hypothesis that seed dormancy may be dependent on environmental conditions and seed morphological traits was tested for six Ribes species, across an altitudinal gradient of 1300 m and a longitudinal separation of 120°. Embryo measurements and seed germination experiments were conducted for R. alpinum L., R. hudsonianum Richardson var. petiolare (Douglas) Jancz., R. nevadaense Kellogg, R. roezlii Regel var. cruentum (Greene) Rehder and R. speciosum Pursh, and data taken from the literature for R. multiflorum Kit. ex Schult. ssp. sandalioticum Arrigoni. Germination was compared with seed viability to reveal proportional seed dormancy, which was then correlated to seed/embryo morphological traits and these traits related to the seed provenance environment. The embryos of all the investigated species are linear underdeveloped and all had a morphological component of seed dormancy (MD). Seeds of R. roezlii, R. hudsonianum and R. nevadaense required a temperature and/or hormone pre‐treatment in order to germinate, highlighting morphophysiological seed dormancy (MPD). Seed dormancy was found to be strongly negatively correlated with embryo length, but not with embryo to seed (E:S) ratio or seed mass. Initial embryo length was positively related to mean annual temperature. Seed dormancy in the investigated Ribes species could be quantified and predicted by the interaction of embryo traits and environmental conditions. This approach may be helpful in assessing and predicting seed dormancy in the Ribes genus and in other genera and families with underdeveloped embryos.